Diseño y construcción de un banco de pruebas de instrumentos de medición en el tratamiento de aguas para la empresa AWT S.A. - Carua Pilicita, Edwin Patricio (2016)
The document refers to the design and construction of a testing bank to monitor and verify the functionality of the various measuring instruments needed in water treatment, thereby allowing the company AWT SA, have highly reliable equipment building their plants. This bank to determine possible failures either electrical activation in data transmission to the respective controller or simply the normal operation of the equipment can monitor each parameter of each element through a HMI (Human Machine Interface), for a certain time required for verification thereof, the interface was done in runtime with the TIA Portal V13 tool, plus a database in Microsoft SQL Server 2008 which can store and download the data stored periodically created. To achieve the goal implied meet their specifications, dimensions and characteristics of each element used, besides the technical analysis of the different instruments used in water treatment and can determine its operation, operating principle and mode of connection was made, which allowed to obtain data necessary for the design of both the mechanical, electrical and electronic plans of the project. The testing bank consists of a control board, the metal structure is constructed of square black structural tube, and the hydraulic system is made of PVC pipe, ball valves and other elements necessary for its operation.